Water resistance and thermal behavior of metakaolin-phosphate-based geopolymer cements - Nobouassia Bewa, Christelle; Tchakouté, Hervé K.; Fotio, Daniel; Rüscher, Claus H.; Kamseu, Elie; Leonelli, Cristina (Journal of Asian Ceramic Societies, 2018)
The main target of this work was to investigate the thermal behavior and water resistance of geopolymer cement made from metakaolin as an aluminosilicate source using phosphoric acid solution (10 M) as a hardener. The obtained geopolymer cements were cured at room temperature for 28 days, the one part was treated at 200°C, 400°C, 600°C, 800°C and 1000°C, and the others were soaked in water for 28 days. The geopolymer cements were characterized by microstructural properties using X-ray diffractometry, infrared spectroscopy, microstructure, physical property based on water resistance and thermo-mechanical properties (thermal analysis, compressive strength). The results show that the compressive strength of the unheated geopolymer cement was 87.96 MPa. The ones soaked in water revealed a strength of 40.71 MPa. This indicates that the specimens soaked in water lose about 54% of their strengths. The X-ray patterns of heated geopolymer cements showed the formation of crystalline phases even at relatively low temperatures. It was typically found that the compressive strength of metakaolin-phosphate-based geopolymer cements decreases due to the hydrolysis of Si-O-P bonds in the presence of water.